On sequentially retractive inductive limits - Armando García (International Journal of Mathematics and Mathematical Sciences)
Every locally complete inductive limit of sequentially complete locally convex spaces, which satisfies Retakh's condition (M) is regular, sequentially complete and sequentially retractive. A quasiconverse for this theorem and a criterion for sequential retractivity of inductive limits of webbed spaces are given.